TELAAH ATAS ADJUDIKASI PUTUSAN KASUS KORUPSI - Widiada Gunakaya (Komisi Yudisial RI, 2010)
ABSTRACTAdjudication is the most important stage in the criminal court system, because at this stage, that the defendant's fault must be proven through a court decision. As the final stage of law enforcement in a criminal court proceeding, court decisions normatively should reflect the material truth. And the decision reviewed in this paper, the defendant has been convicted guilty of